A concept for a potential metric to characterise the dynamic thermal performance of walls - Alterman, Dariusz; Moffiet, Trevor; Hands, Stuart; Page, Adrian; Luo, Caimao; Moghtaderi, Behdad (Energy and buildings, 2012)
A novel concept for characterising the dynamic thermal response (T-value) of walling systems to assist with the evaluation of the thermal performance of walling systems, and possibly housing, takes into account the mechanisms involved between various components of a wall, as well as the complete building envelope, which jointly respond to external environmental variations. The concept has been validated through analysis of the performance of various housing systems at the University of Newcastle, Australia and a detailed study of building response to changing environmental conditions. Current design practice is to characterise the potential thermal performance of a building interior by emphasising the thermal resistances (R-values) of the various building elements. However, the statically determined nature of the R-value cannot adequately relate the dynamic thermal response of a wall (or building interior) to external thermal changes. The concept for a comprehensive new metric for dynamic performance which considers the ordered combination of the insulation and thermal mass properties of the elemental layers within the particular wall type(s) is presented. It can be applied to walls and/or building envelopes.